Effect of Fly Ash Fortification in the Manufacture Process of Making Concrete towards Characteristics of Concrete in Sulfuric Acid Solution - Saputra, Asep Handaya; Shohibi, Muhammad; Kubouchi, Masatoshi (UI Scholars Hub, 2015)
Fly ash is a silica or alumino silica material that can be used as a constituent of cement in the concrete manufacturing process. Utilization of fly ash aims to improve durability and minimize the reduction of concrete’s compressive strength exposed to an acidic environment, which can be achieved through the pozzolanic reaction of fly ash with Ca(OH)2 within concrete. The reduced content of Ca(OH)2 through pozzolanic reaction will minimize the tendency of ettringite formation (compounds that cause deterioration and decrease the compressive strength of concrete). In order to determine the relation between fly ash replenishment into concrete with concrete’s characteristics (compressive strength and durability) under acidic environment, the research is conducted by varying the fly ash composition ranging from 0%, 5%, 25%, 50%, up to 75%, and the concentration of H2SO4 solution as an immersion medium ranging from 0%, 5%, 10%, up to 15% (v/v). The research is carried out by immersing the concrete samples for 4 days in H2SO4 solution with various concentrations. Characterization of concrete’s durability and compressive strength is reviewed from the concrete’s weight loss percentage and reduction of concrete’s compressive strength percentage after immersion. Based on the research results, for each variation of H2SO4 concentration used, the minimum concrete’s weight loss percentage (maximum durability) and the minimum reduction of concrete’s compressive strength percentage is found in the use of fly ash by 75%. For each concentration variations of H2SO4 solution as an immersion medium ranging from 5%, 10%, up to 15% (v/v), the minimum concrete’s weight loss percentage was 0.47%, 0.87%, 1.28% (respectively), whilst the minimum reduction of concrete’s compressive strength percentage was 5.71%, 14.29%, 17.14% (respectively). It was concluded that the use of fly ash can improve the durability and minimize the reduction of compressive strength of concrete exposed to an acidic environment.